REGIONAL FEATURES OF THE NATIONAL PROJECTS IMPLEMENTATION AND THE ROLE OF CONTROL AND ACCOUNTING BODIES OF OF THE RUSSIAN FEDERATION SUBJECTS IN THE TRANSITION TO PROJECT MANAGEMENT - M. R. Kara-Sal; V. K. Khomushku (Вестник университета)
The features of the implementation of project management in the executive authorities of the Republic of Tuva have been considered and the essence of the regional project management system has been revealed. Problems during the implementation of national projects in the Republic of Tuva, as well as during monitoring of their implementation, including the problem of access to relevant information on the development, implementation, reporting on the implementation of regional projects have been studied. Based on the study, it has been concluded that it is necessary to manage state programs and projects from the perspectives of a systematic approach. It is necessary to organize a system of access to relevant information on the development, implementation, reporting on the implementation of regional projects, amending the law of the Republic of Tuva “On the Accounting Chamber of the Republic of Tuva”, providing for access to information systems and resources, as well as developing a standard for external state financial control “Monitoring regional projects”.